Multimodality and argumentation on the genre Reportage - Leal, Audria (2018)
This paper aims to study the role of the visual in the argumentation used in the genre news report. For this purpose, we look at two texts of this genre from the Portuguese magazine Visão. Our analysis is based on the theoretical assumptions of Social Semiotics, including the methodological framework of the Grammar of Visual Design. In fact, the present paper seeks to consider the role of the non-verbal dimension in the genre news report and also in relation to the social function of this genre.The results indicate that the meanings of the visual representations participate as arguments in the news report and they are built from the social practices to fulfil the communicative function of the genre.